Providing Feedback from Experiences in Conducting Clinical Competency Exam for the General Dentistry Courses - Mehrdad Shahraki; Sadra Amirpourharadasht; Mohammad Rasoul Asadi (Journal of Medical Education and Development)
The main aim of any educational system is the successful completion of the learning process, and one of the ways to achieve this goal is to provide effective feedback to students about their activities during the learning period. Feedback is considered the main source of change in student performance and is valuable when it shows the difference between the desired results and the actual results of student performance and stimulates change. After passing several crucial and decisive exams, medical and dental students graduate and with all the achievements, receive a license to begin their independent professional activities.